CLUSTERS IN NATIONAL INNOVATION SYSTEMS - O. D. Gaisha (Вестник университета)
The experience of developed countries demonstrates the use of the cluster concept as an effective tool, that promotes the development of entrepreneurship and innovations, improving the competitiveness of both individual regions of clusters and the country as a whole. As analysis result of indicators of innovation development and competitiveness of countries, a close link was noted between the factors under study. This circumstance confirms the importance of the cluster concept in the development of national innovation systems. As part of the study were used the methods of bibliographic and logical analysis, as well as the method of linear correlation and regression analysis.